Evaluate the effect of mutans Aspergillus niger to the nutritive value of fermentation at coconut meal and karnel palm meal - LAELA SARI; TRESNAWATI PURWADARIA (Society for Indonesian Biodiversity, 2004)
Agricultural wastes, such as coconut meal and kernel palm meal can be used to fulfill the need of feed for ruminants ormonogastrics. Fermentation technology using Aspergillus niger has been reported allow to increase their nutritive value.Isolation of the asporogenous strain which could spored at room temperature but could not spored at 37oC is expected to sole the fermentation of spores in the fermentation product. The spore formation of mutants at the fourth day incubationtime (10%) was less than the wild type (100%). The variance analysis of protein content in vitro Dry Matter Digestibility (IVDMD) and in vitro Protein Digestibility (IVPD) showed that the kind of mutants were interacted with the incubation time(P<0,01). The highest protein content of coconut meal was obtained from E27 mutant (33.0%), kernel palm meal wasobtained from E14 mutant (31.4%) at the fourth day of incubation time. The highest IVDMD of coconut meal (62.1%), kernel palms meal (61.8%) at the fourth day incubation time and from all E27 mutant. The highest IVPD of coconut meal was obtained from E27 mutant (20.49%) at the fourth day incubation time, kernel palm meal was obtained from E27 mutant (18.66%) at the fourth days incubation time.Â© 2004 Jurusan Biologi FMIPA UNS SurakartaKeywords: mutant Aspergillus niger, coconut meal, kernel palm meal, fermentation